Endovascular treatment of a sacral dural arteriovenous fistula. Issue 2 (5th February 2021) - Porwal, Mokshal H; Tutton, Sean; Sinson, Grant P; Sacho, Raphael
Abstract : Spinal dural arteriovenous fistula (SDAVF) is a rare pathological communication between arterial and venous vessels within the spinal dural sheath. Clinical presentation includes progressive spinal cord symptoms including gait difficulty, sensory disturbances, changes in bowel or bladder function, and sexual dysfunction. These fistulas are most often present in the thoracolumbar region. Diagnoses of SDVAFs are commonly missed, possibly due to the low index of suspicion, non-specific symptoms and challenging imaging. In this case report, we describe a rare presentation of a sacral SDAVF which was detected by collective efforts between endovascular neurosurgery and interventional radiology. We outline the diagnostic and imaging challenges we faced to discover the fistula. In particular, mechanical pump injection instead of hand injection during angiography was required to reveal the fistula. Following identification, the fistula was successfully treated endovascularly by using onyx (ethylene vinyl alcohol glue), a less invasive alternative to surgical intervention.